Prognostic value of lactate in cats presented in respiratory distress to the emergency room - Gilday, Cassandra; Guieu, Liz (Frontiers in Veterinary Science, 2022)
Studies demonstrating the prognostic utility of plasma lactate concentration and lactate clearance in cats are limited. The objective of this study was to determine the prognostic utility of plasma lactate concentration upon admission and plasma lactate clearance in cats presented to the emergency room with respiratory distress attributed to underlying cardiac or respiratory disease. Additionally, we sought to determine if plasma lactate concentration on admission was significantly associated with underlying cause of respiratory distress (cardiac vs. respiratory), type of respiratory disease and vital parameters. Seventy-one cats presented in respiratory distress to the ER at a university teaching hospital were enrolled in this retrospective study. Admission lactate concentration was not associated with survival, duration of hospitalization, vital parameters nor underlying etiology for respiratory distress. In contrast, lactate clearance was significantly associated with survival and length of hospitalization. While a statistically significant association between lactate clearance and length of hospitalization was identified, this finding lacked clinical significance where an increase in lactate concentration by 1% was associated with an increased length of hospitalization by 11.4 minutes (p=0.035). Results of this study suggest that lactate clearance may have prognostic utility in this population of cats. Further studies including larger population of cats with underlying cardiac or respiratory disease are warranted.